Fetish Again?: Southern Perspectives on the Material Approach to the Study of Religion - Appiah, Simon Kofi (Open theology, 2022)
The material turn in the study of religions has opened new methodological vistas, rejuvenating the notion of fetish . Scholars in Africa must acknowledge and share in the successes of the material approach. At the same time, they cannot help but recall that in colonial Africa the notion of fetish was, par excellence, the mirror of primitive religion and the denigration of Africans in the missionary enterprise. Fetish was not only the medium for the fall of African religions and the enforcement of colonial authority, but also and especially, the genesis of the theory of primitive religions. This paradox looms large when the material turn is re-read from southern perspectives as a call for a radical intra-cultural critique of the epistemological positions and subalternity of knowledge production in Africa.